Explaining Student Intention to Use E-Learning Policy in Coastal and Archipelagic Regions: The Role of Facilitating Conditions and Trust - Dedy Afrizal; H. Hildawati; Ilham Yuri Nanda; Dina Purnamasari; M. Tazri; Latifah Gusri; Ida Rahayu; Yusuf Velandi (Manunggal Halim Jaya, 2026)
The digitalization that has occurred has changed the way universities in Indonesia implement the learning process. The government's push for e-learning the best solution for students and lecturers to carry out their learning activities. The emergence of a series of innovative findings related to online learning would certainly provide the government with insight into formulating regulations in the face for Students in the Coastal Area. The findings of research on the usage of information technology are not limited to universities as service providers, as well as on the student intentions of technology users. This paper will investigate how students intend to use e-learning in in the Coastal Area. Quantitative approach was conducted in Riau Island Province, involving 150 students. The main construct of the UTAUT Model, was studied and tested with Structural Equation Modeling. The results of the analysis show that only Facilitating Conditions and Trust have a positive and significant effect on the intention to use e-learning. The study suggests to government should prioritize improving the equitable distribution of technological infrastructure and internet accessibility, particularly in coastal areas, small islands, and border regions within the Riau Islands Province.